1995
DOI: 10.1002/1097-0142(19950515)75:10<2499::aid-cncr2820751016>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous melanoma. Optimized cutoff points of tumor thickness and importance of clark's level for prognostic classification

Abstract: Background. Maximum tumor thickness and level of invasion are known to be the most important prognostic factors for patients with primary cutaneous melanoma. However, the classification of tumor thickness and the question of whether the combination of tumor thickness and level of invasion provides a better prognostic classification than tumor thickness alone are still matters of debate. The present study examined the relationship between tumor thickness and survival probability to define cutoff points of tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(56 citation statements)
references
References 25 publications
5
45
0
6
Order By: Relevance
“…In particular, if the tumor thickness exceeds 3.5 mm, it loses predictive power. 25 We conclude that in neuroectoderm-derived cancers, melanocytic tumors and glioblastomas, overexpression of the cell cycle controller pRb is limited to the malignant phenotype. pRb is markedly overexpressed in actively growing parts of malignant melanomas and coincident with hyperphosphorylation and possible pRb inactivation.…”
Section: Discussionmentioning
confidence: 86%
“…In particular, if the tumor thickness exceeds 3.5 mm, it loses predictive power. 25 We conclude that in neuroectoderm-derived cancers, melanocytic tumors and glioblastomas, overexpression of the cell cycle controller pRb is limited to the malignant phenotype. pRb is markedly overexpressed in actively growing parts of malignant melanomas and coincident with hyperphosphorylation and possible pRb inactivation.…”
Section: Discussionmentioning
confidence: 86%
“…6 One German database showed that a Clark level III tumor had a 3.5 times greater risk of disease progression than did a level II tumor in melanomas r1.0 mm in thickness. 57 …”
Section: Thickness (Breslow)mentioning
confidence: 99%
“…However, we did not observe significant changes in SOX2 expression at different stages of disease progression (Figure 1b). Breslow depth, which is defined as the total vertical height of the tumor, is one major important prognostic predictor of death from melanoma 29,30 . Therefore, we plotted SOX2 expression from human primary melanomas to Breslow thickness.…”
mentioning
confidence: 99%